Pathogenesis of indirect (secondary) acute lung injury. (February 2011) - Perl, Mario; Lomas-Neira, Joanne; Venet, Fabienne; Chung, Chun-Shiang; Ayala, Alfred
At present, therapeutic interventions to treat acute lung injury (ALI) or acute respiratory distress syndrome (ARDS) remain largely limited to lung-protective strategies, as no real molecular––pathophysiologic-driven therapeutic intervention has yet become available. This is in part the result of the heterogeneous nature of the etiological processes that contribute to the state of ALI/ARDS. This article sets out to understand the development of ALI resulting from indirect pulmonary insults, such as extrapulmonary sepsis and trauma, shock, burn injury or mass transfusion, as opposed to direct pulmonary challenges, such as pneumonia, aspiration or lung contusion. Here, we consider not only the experimental and clinical data concerning the roles of various immune (neutrophil, macrophage, lymphocyte and dendritic) as well as nonimmune (epithelial and endothelial) cells in orchestrating the development of ALI resulting from indirect pulmonary stimuli, but also how these cell populations might be targeted therapeutically.